A Review of Treatment of Schizophrenia in Children and Adolescents - Yongmei, Hou (Achievements and Challenges of Medicine and Medical Science Vol. 3, 2024)
Objective: The primary objective of the study is to understand the current research status of treatments for schizophrenia in children and adolescents, and to clarify their effectiveness and shortcomings. Methods: We searched CNKI, Embase, Medline, and PsycInfo databases for systematic reviews, or randomized controlled trials (RCTs) of pharmaceutical and non-pharmaceutical interventions implemented in patients with childhood or adolescent onset schizophrenia. Results: Forty-eight articles were suitable for this review. The safety of antipsychotic drugs has not been fully determined though pharmacological therapy is generally considered to have a fast onset and significant therapeutic effect. Electroconvulsive therapy (ECT) has good efficacy and few adverse reactions, especially for symptoms of tension and stiffness, but it has strict indications and operational requirements. Repetitive transcranial magnetic stimulation (rTMS), transcranial direct current stimulation (tDCS), and music therapy can increase cortical excitability, and improve the morphology of brainwaves and cognitive function, but clinical studies are limited. Clinical practice has shown that psychotherapies can reduce positive and negative symptoms, alleviate emotional disorders, correct cognition and personality, and promote social rehabilitation, their effectiveness needs to be confirmed by evidence-based medicine. Conclusion: Each therapy has its own advantages and disadvantages, and comprehensive treatments should be adopted according to the condition.